How Do Plurilingual Teacher Trainees View the CLIL Challenge? A Case Study - Cerezo Herrero, Enrique; García-Bellido, Rosario (Miscelánea: A Journal of English and American Studies, 2021)
The Valencian region is a Spanish autonomous community with a long-standing tradition in bilingual education. However, as opposed to some other Spanish regions, attention towards the linguistic education system from the point of view of research has been scarce. On this basis, the present investigation seeks to analyze the plurilingual education system of the Valencian region currently in force from the perspective of trainee teachers.To this end, a study has been conducted with three focus groups. The narrative produced by the participants has been analyzed taking into consideration four major dimensions, namely plurilingual programs, teacher training, methodology, and resources and materials. In this analysis, the main idea underlying each dimension has been identified and then the information has been synthesized in flow charts that broadly represent the information conveyed by the groups.The results obtained evince a lack of initial and continuous teacher training in plurilingual issues, a reality which translates into a low level of linguistic competence and methodological lacunae, as well as a lack of tailored-made teaching materials. There is thus an urgent need to revisit major aspects of the plurilingual programs and bring about certain changes that could contribute to their improvement and consolidation.